Applications of Biocompatible Scaffold Materials in Stem Cell-Based Cartilage Tissue Engineering - Zhao, Xia; Hu, Daniel A.; Wu, Di; He, Fang; Wang, Hao; Huang, Linjuan; Shi, Deyao; Liu, Qing; Ni, Na; Pakvasa, Mikhail; Zhang, Yongtao; Fu, Kai; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Cartilage, especially articular cartilage, is a unique connective tissue consisting of chondrocytes and cartilage matrix that covers the surface of joints. It plays a critical role in maintaining joint durability and mobility by providing nearly frictionless articulation for mechanical load transmission between joints. Damage to the articular cartilage frequently results from sport-related injuries, systemic diseases, degeneration, trauma, or tumors. Failure to treat impaired cartilage may lead to osteoarthritis, affecting more than 25% of the adult population globally. Articular cartilage has a very low intrinsic self-repair capacity due to the limited proliferative ability of adult chondrocytes, lack of vascularization and innervation, slow matrix turnover, and low supply of progenitor cells. Furthermore, articular chondrocytes are encapsulated in low-nutrient, low-oxygen environment. While cartilage restoration techniques such as osteochondral transplantation, autologous chondrocyte implantation (ACI), and microfracture have been used to repair certain cartilage defects, the clinical outcomes are often mixed and undesirable. Cartilage tissue engineering (CTE) may hold promise to facilitate cartilage repair. Ideally, the prerequisites for successful CTE should include the use of effective chondrogenic factors, an ample supply of chondrogenic progenitors, and the employment of cell-friendly, biocompatible scaffold materials. Significant progress has been made on the above three fronts in past decade, which has been further facilitated by the advent of 3D bio-printing. In this review, we briefly discuss potential sources of chondrogenic progenitors. We then primarily focus on currently available chondrocyte-friendly scaffold materials, along with 3D bioprinting techniques, for their potential roles in effective cartilage tissue engineering. It is hoped that this review will serve as a primer to bring cartilage biologists, synthetic chemists, biomechanical engineers, and 3D-bioprinting technologists together to expedite cartilage tissue engineering process for eventual clinical applications.